Studi Kepuasan Konsumen Pada Honda AHASS di Semarang - Mochamad Hangga Novian (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to analyze the effect of service quality and brand image on customer satisfaction at Honda AHASS Semarang. Data was collected through a survey of 45 respondents who are customers of Honda AHASS Semarang. The data analysis technique used is product moment analysis and multiple correlation. The results showed that service quality and brand image together had a significant effect on customer satisfaction. Service quality has a greater influence than brand image. The dimension of service quality that has the most influence on customer satisfaction is the reliability dimension, then the dimensions of responsiveness, assurance, empathy, and finally the caring dimension. The implication of this research is that Honda AHASS in Semarang needs to continue to improve its service quality, especially in the dimensions of reliability, responsiveness, assurance, empathy, and care. In addition, Honda AHASS in Semarang also needs to maintain its brand image to remain positive in the eyes of consumers.